2018
DOI: 10.1111/jeb.13367
|View full text |Cite
|
Sign up to set email alerts
|

Resource stability and geographic isolation are associated with genome divergence in western Palearctic crossbills

Abstract: While many conifers produce annually variable seed crops, serotinous species (which hold seeds in cones for multiple years) represent unusually stable food resources for seed predators. Such stability is conducive to residency and potentially population divergence of consumers as exemplified by the Cassia crossbill (Loxia sinesciuris) in North America. We used genotyping by sequencing (GBS) to test whether three Mediterranean subspecies of common crossbills (L. curvirostra) associated with the serotinous Alepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 99 publications
1
13
0
Order By: Relevance
“…These results suggest that the same drivers of differentiation are acting in the western Palearctic north of 44°N as in the south, yet under different circumstances. This result is confirmed by Parchman et al (), who found that red crossbills living in geographically isolated areas with a stable food resource (here Pinus halepensis ) were genetically distinct from other red crossbills.…”
Section: Discussionsupporting
confidence: 72%
“…These results suggest that the same drivers of differentiation are acting in the western Palearctic north of 44°N as in the south, yet under different circumstances. This result is confirmed by Parchman et al (), who found that red crossbills living in geographically isolated areas with a stable food resource (here Pinus halepensis ) were genetically distinct from other red crossbills.…”
Section: Discussionsupporting
confidence: 72%
“…[135,136], Fringilla coelebs [137,138], and Loxia spp. [139]. Similarly deep splits between Iberian and Maghrebian populations of the same species were PLOS ONE found in other terrestrial vertebrates, such as in amphibians, reptiles [25,140], and in mammals [141][142][143][144].…”
Section: Phylogeographic Patterns In the Ibero-maghrebian And Cyrenaimentioning
confidence: 72%
“…Genomic research is underway to determine to what extent this ecological specialization and morphological divergence is linked to genetics. Preliminary results already have shown that genetic differences between presumably conspecific Crossbill populations within Spain are far greater than between heterospecific Common and Parrot Crossbills (Parchman et al 2018). In view of the potential for movement and habitat selection by Crossbills, it is important to improve our understanding of dispersal of these birds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While Mezquida and Benkman (2005) noted that these cones appeared to have evolved levels of defence that have excluded Crossbills foraging on this pine, Crossbills are indeed not common, but are nonetheless rather widespread in Aleppo Pine forests. Genetic data indicate they are apparently resident, at least in southern Iberia, and presumably only forage on Aleppo Pine cones just as on the Balearics and in northern Africa (Parchman et al 2018). We have confirmed here that they have a distinct biometry, suggesting they are well adapted to this mainland Aleppo Pine variety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation